New Trends in Dermoscopy to Minimize the Risk of Missing Melanoma - Aimilios Lallas; Zoe Apalla; Georgios Chaidemenos (Journal of Skin Cancer)
During the last decades, induction of dermoscopy in the clinical setting resulted in significant modifications in the management of melanocytic lesions. Indeed, the dermatoscope reveals a fascinating world of morphologic structures invisible to the naked eye, adding valuable information to a clinician evaluating a mole. However, since the technique counts only a couple of decades, new research data are continuously gathering and modify the “optimal” management of melanocytic lesions. In the present paper, we summarize the latest trends in dermoscopy concerning early melanoma diagnosis, management of nodular lesions, diagnosis of mucosal melanoma, and digital followup.